Ultrasound diagnosis of intrauterine growth retardation. - Koremblit, Norman (2015)
In recent years we have witnessed a movement of general interest in fetuses with intrauterine growth difficulties. The wake-up call which means Intrauterine Growth Restriction (IUGR), for obstetricians, pediatricians, and Perinatologists, is highly justified, as it represents a high perinatal mortality (8 times higher than those of normal weight). Frequent acute and chronic fetal distress, the many dangers in the neonatal period, and possible subsequent subnormality, are listed in the growing research on this topic.